The limits of responsibility in liberal egalitarian theory. - Blahuta, Jason P. (University of Ottawa (Canada), 2002)
The critical object of this dissertation is to show that major liberal (and libertarian) theories of distributive justice are unsatisfactory because they rely on highly problematic conceptions of the self. What is problematic is that, in one way or another, they cannot support a proper conception of individual autonomy and personal responsibility. Constructively, the project therefore seeks to sketch a conception of the self that will reconcile as far as possible individual autonomy, and personal responsibility, with egalitarian concerns in distribution. The practical outcome is a revised version of the starting-gate theory, that is, the theory holding that a just distribution of wealth can only be achieved through restricting inequalities in earnings and wealth by the need to preserve ongoing conditions of equality of opportunity, but by no more than that. Thus, the most general theme of the dissertation is the foundational role of theories of the self for conceptions of economic distribution; the connecting element and argumentative strategy centers, both critically and constructively, on notions of individual autonomy and personal responsibility; and the specific positive result is advocacy of a version of the starting-gate theory because of its suitable underlying or implied conception of the self as regards individual autonomy and responsibility.
Keywords: Philosophy.